Serogroup A meningococcal conjugate (PsA-TT) vaccine coverage and measles vaccine coverage in Burkina Faso—Implications for introduction of PsA-TT into the Expanded Programme on Immunization. Issue 12 (17th March 2015) - Meyer, Sarah A.; Kambou, Jean Ludovic; Cohn, Amanda; Goodson, James L.; Flannery, Brendan; Medah, Isaïe; Messonnier, Nancy; Novak, Ryan; Diomande, Fabien; Djingarey, Mamoudou H.; Clark, Thomas A.; Yameogo, Issaka; et al.
Highlights Evaluation of MCV coverage will help guide successful PsA-TT introduction into EPI. A national survey was conducted in Burkina Faso to assess PsA-TT and MCV coverage. PsA-TT campaign coverage was 95.9% with coverage greater than 90% in all regions. Routine MCV coverage was 92.5%, but varied from 75.3% to 95.3% by region. Results identify regions at-risk for future suboptimal PsA-TT EPI coverage.